EFEKTIVITAS PELAKSANAAAN JOB SAFETY ANALYSIS (JSA) SEBAGAI UPAYA PENCEGAHAN VIRUS CORONA DIMASA PANDEMI COVID-19 PADA KANTOR PT. PRAJA GHUPTA UTAMA - Nauffal Priyambodo (FT-USNI, 2021)
PT. Praja Ghupta Utama is a company engaged in the contracting sector with the experience and resources to provide the best service in the construction sector. The purpose of this study was to analyze the effectiveness and potential hazards, assess risks, control risks at the head office during the Covid-19 pandemic. The process of office activities carried out by PT. Praja Ghupta Utama has the possibility of a high risk of exposure to the workspace area. Therefore, potential hazards must be analyzed with one of the risk analysis methods, namely JSA (Job Safety Analysis). The JSA method is used to analyze existing hazards, determine risk assessments and classify each hazard based on its risk level. The JSA method can reduce the potential for work accidents by managing a series of activities carried out. PT. Praja Ghupta Utama applies elimination controls, modification techniques, and personal protective equipment (PPE) to reduce exposure or accidents and risk management and also has excellent results in knowledge and behavior related to occupational safety and health and good on knowledge of JSA.